Determination of the coenzyme Q10 status in a large Caucasian study population. (31st July 2015) - Onur, Simone; Niklowitz, Petra; Fischer, Alexandra; Jacobs, Gunnar; Lieb, Wolfgang; Laudes, Matthias; Menke, Thomas; Döring, Frank
Abstract Coenzyme Q10 (CoQ10) exists in a reduced (ubiquinol) and an oxidized (ubiquinone) form in all human tissues and functions, amongst others, in the respiratory chain, redox‐cycles, and gene expression. As the status of CoQ10 is an important risk factor for several diseases, here we determined the CoQ10 status (ubiquinol, ubiquinone) in a large Caucasian study population (n = 1, 911). The study population covers a wide age range (age: 18–83 years, 43.4% men), has information available on more than 10 measured clinical phenotypes, more than 30 diseases (presence vs. absence), about 30 biomarkers, and comprehensive genetic information including whole‐genome SNP typing (>891, 000 SNPs). The major aim of this long‐term resource in CoQ10 research is the comprehensive analysis of the CoQ10 status with respect to integrated health parameters (i.e., fat metabolism, inflammation), disease‐related biomarkers (i.e., liver enzymes, marker for heart failure), common diseases (i.e., neuropathy, myocardial infarction), and genetic risk in humans. Based on disease status, biomarkers, and genetic variants, our cohort is also useful to perform Mendelian randomisation approaches. In conclusion, the present study population is a promising resource to gain deeper insight into CoQ10 status in human health and disease. © 2015 BioFactors, 41(4):211–221, 2015